Implementasi Sistem Penunjang Keputusan Penentuan Peringkat Terbaik Sekolah Menengah Atas Menggunakan Metode TOPSIS di Jakarta Selatan - Farhan Septian; Sofa Sofiana (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study applies the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to determine the best ranking of Senior High Schools in South Jakarta. The aim of this research is to develop a web-based decision support system that assists the school assessment process in an objective, measurable, and transparent manner. The TOPSIS method was chosen because it can compare each alternative based on its distance to the positive and negative ideal solutions, resulting in more accurate rankings. The criteria used include the UTBK score, school accreditation, teacher-to-student ratio, and transportation access. The data were processed through the stages of decision matrix construction, normalization, weighting, positive and negative ideal solution determination, distance calculation, and preference value determination to produce the best ranking results. The system was built using PHP and MySQL and was tested using Black Box and White Box testing. The results show that the application of the TOPSIS method provides consistent calculations aligned with the assessment criteria, with alternative A2 obtaining the highest preference value of 0.820. The developed system can clearly and easily display ranking results while minimizing subjectivity in decision-making, so it can serve as an effective tool in evaluating the quality of education in South Jakarta.